Use of Safety Pin on Garments in Pregnancy: A Belief and Cultural Practice with Potential Harmful Effect - Kola M Owonikoko; Aramide M Tijani; Olarewaju G Bajowa; Oluseyi O Atanda (AIMS Press, 2017)
Background: Culture has been known to influence practices and beliefs of people world over. Several cultural practices have been noted among pregnant women who were passed from one generation to the next with its potential harmful and beneficial effect. The use of safety pin in is one of such cultural practices that are widely practiced by many pregnant Nigerian women. Objective: We sought to gain a deeper understanding of the source of knowledge and motivation behind the use of safety pin on garments during pregnancy as well as explore potential harmful side effects of this cultural practice. Methodology: A total of 419 pregnant women completed questionnaires for a hospital-based cross-sectional study. Safety pin knowledge and motivation for use on garments were assessed using a pre-tested 16 item questionnaire. Consenting women either completed a self-administered structured questionnaire or utilized the help of trained research assistants. Chi-square tests were used to assess relationships between safety pin use on garments and predictor variables. Analysis was done with Statistical Package for Social Sciences version 17. Results: Of 419 participants, over half (n = 227) reported safety pin use on garments in pregnancy. About two-thirds (n = 177) of women who use safety pin reported older female relatives as their source of information. The mean age of the participants was 29.1 ± 5.74 (range 16-45 years). Traditional religion worshippers were more likely (81.2%) and Christians were least likely to use safety pin (50.7%) during pregnancy. Pregnant women with a tertiary education (50.4%) were least likely to use safety pin compared with women with no or less than a tertiary level of education. Protection of pregnancy against demons/witchcrafts was the reason given by 129 (56.8%) of participants using safety pin in pregnancy. Conclusion: The use of safety pin on garments during pregnancy is a common cultural practice in southwest Nigeria. Our findings also suggest that religion and education are important determinants of safety pin use. Although our study did not find a statistically significant difference in safety pin prick incidents among safety pin users, it remains a potential source of harm. Thus, there is a need to establish community and hospital based strategies that address potential cultural harmful practices while promoting culturally appropriate healthcare services.